Implementasi Peraturan Menteri Keuangan Nomor 214/PMK.01/2011 (Studi pada Kantor Pelayanan Perbendaharaan Negara Kudus) - Asih Widi Lestari (Universitas Muhammadiyah Sidoarjo, 2015)
The purpose in this research is to describe and analyze implementation of Finance Ministry Regulation Number 214/PMK.01/2011 about Discipline Enforcement Based on Remuneration/ Special allowance of State Financial Guidance at Finance Ministry Area, the support and inhibitor factors, and impact of this regulation to increase discipline civil servants in KPPN Kudus. This research is using descriptive qualitative method. The implementation of Finance Ministry Regulation Number 214/PMK.01/2011 in KPPN Kudus was successfully, it viewed from actors, mechanism and handkey. This regulation has positive impact to increase discipline civil servants in KPPN Kudus. The support factors is the contents of the regulation is detail; the attitude civil servants in KPPN Kudus is willing to receive all provisions contained in regulation; and the comfortable conditions in KPPN Kudus. Inhibitor factors is a outside factors is alleged happened to civil servants; and the workload of a caretaker is too overload. But still there was a cleft in this Finance Ministry Regulation Number 214/PMK.01/2011, this is no regulated about rest hours in this regulation, so needed improvement in this regulation with make provision of electronic absent in rest hour.